Survey on knowledge and herbal intake among patients with elevated level of hepatic transaminase enzymes in medical ward HUSM - Khairunnisa, Abas (Universiti Sains Malaysia, 2009)
The purposes of this study are to determine the knowledge of herbal safety among patients with elevated level of Hepatic transaminase enzymes, to detennine the type of herbal taken among patients and to examine the significant difference in alanine transaminase (AL T) and aspartate transaminase (AST) levels between patients in medical ward HUSM who take and do not take herbal. The use of traditional medication in Malaysia has increased from year to year and people now get more attracted to use a traditional medication like herbs in their health care although, the data about herbal intake and their safety in Malaysia are still lacking. This study recruited 50 patients as its respondents from medical ward and clinic in HUSM from July 2008 to March 2009. The research design used in this study was descriptive cross sectional design. This design was used to collect quantitative data. Descriptive statistic and non-parametric Mann Whitney U test were used in this study to analyze the data. The age of respondents are ranging from 30 years old to 90 years old. From the 50 respondents, (74%, n=50) of them were taking herbs while (26%, n=50) did not take herbal. From this study, the percentage of accurate knowledge regarding herbal safety is lower than the percentage of inaccurate knowledge among the respondent. Therefore, there is no knowledge regarding herbal safety among the respondents. There are significant difference in AL T and AST between patient take herbal or not (ALT, p = 0.04, AST, p = 0.02).